Design and simulation study of obstacle based passive micromixer - Zulkarnain, Maizul Haffin (2013)
Micromixer can be dividing by two categories which are active micromixer and passive micromixer. Due to simple fabrication technology and the easy implementation in a complex microfluidic system, obstacle based passive micromixers will be the focus of this project. Due to laminar flow (Reynold Number < 1) passive micromixer is the best method in fluids mixing. Passive micromixers also depend on the channel geometry for mixing effectiveness. In this study, seven different micromixers were evaluated based on the baseline control Y micromixer. The micromixers are Y shape with obstacle as proposed in PS 1 micromixer, Y shape with internal rib micromixer, Y shape with obstacle design 2, Y shape with obstacle design 3, Y shape with obstacle design 4, and Y shape with obstacle design 5. These micromixers has 237μm channel length, 30μm inlet length, 90 between inlets ports, width and depth are 30μm each. The fluids used for mixing were blood which has 3.0 × 10-3 kg/μms of viscosity and glycerin which has high viscosity than blood (1.49 × 10-3 kg/μms). The fluids used to evaluate the differences in term of their visual performance based image’s standard deviation by plotting the graph and mixing efficiency by calculation. Based on these evaluations, the Y shape with obstacle design 5 micromixers is the best micromixer design with the highest mixing efficiency of 100% at the outlet of the channel.